Reinternações psiquiátricas no Rio Grande do Norte: implicações e impacto das novas estratégias de atenção à saúde mental - Ramos, Déborah Karollyne Ribeiro (2011)
The Brazilian Psychiatric Reform based on the desinstitucionalization of the assistance, translated to the emphasis on community/territorial treatment and in the social inclusion of the mental suffering, promoted advances in the psychiatric restructuring. In the Rio Grande do Norte (RN), we can enumerate as advances of the Brazilian Psychiatric Reform the expansion of the mental health care chain and the implementation of some strategies that, together, aims to further the psychosocial attention of the individual with psych suffering and to reduce the indices of psychiatrics readmissions in the state. In the current Brazilian‟s mental health situation we were interesting in answered the following question: what the impact of the substitutes services‟ extension in the revolving door phenomenon? This search aims to analyze the revolving door phenomenon occurrences based on the news strategies of mental health care in the Rio Grande do Norte. This is a descriptive-exploratory study with a qualitative approach, oriented by the theoretical framework of critical-dialectical approach about the Brazilian Psychiatric Reform and using the thematic oral history as method of information collects. The search was realized on the Hospital João Machado (HJM), estate reference in psychiatric treatment, and the participants was 20 professionals that work on it. The collection of information had started after the approval of the UFRN Research Ethics Committee with the opinion number 216/2011 and CAAE number 0021.0.051.000-11 and was realized using the direct observation and semi-structured interview. The study‟s results were categorized in two categories and five subcategories of analysis. CATEGORY 1) Current situation of the mental health care chain in the RN, with the subcategories: 1.1 Impact of the new services of mental health care in the revolving door phenomenon in the RN; 1.2 Implications of the new services of mental health care in assisting user to the HJM; 1.3 Issues the permeate the mental health care chain in the RN. CATEORY 2) Main causes of the revolving door phenomenon in HJM, with the categories: 2.1 Family problems; 2.2 Lack of assistance after discharge from psychiatric hospital. In summary, we conclude that the extension of the mental health care chain contributed for the reduction of the psychiatrics re-hospitalization‟s indices in RN. However, we realized that territorial services of mental health care are not the only responsible for the revolving door phenomenon. Factors as family problems and the disarticulation of the assistance after the discharge from hospital influence on the perpetuation of hospitalizations and re-hospitalizations in the local scenario. To study the revolving door phenomenon that occur in the psychiatrics‟ assistance considering the news strategies of mental health care allowed us to approach the advances and challenges brought by the RPb and by the desinstitucionatization in the state, indicating the need for further discussions and problem-solving strategies of psychosocial care.